IGEM:Stanford/2010/Notebook/15 April 2010

From OpenWetWare

(Difference between revisions)
Jump to: navigation, search
(DNA-ligand binding)
(DNA-ligand binding)
Line 15: Line 15:
Solving, we get:
Solving, we get:
-
[DNA-L] = [TotalDNA][L]/(k_on/k_off + L)
+
[DNA-L] = [TotalDNA][L] / (k_off/k_on + L)
 +
 
 +
Usually, we define the dissociation constant to be:
 +
kD = k_off/k_on
 +
 
 +
So we end up with:
 +
[DNA-L] = [TotalDNA][L] / (kD + L)

Revision as of 00:29, 16 April 2010

Journal Club 4/15/10

Presentation by ...

DNA-ligand binding

d[DNA-L]/dt = k_on*[DNA][L] - k_off*[DNA-L]

If we define: [TotalDNA] = [DNA] + [DNA-L]

Then: d[DNA-L]/dt = k_on*([TotalDNA] - [DNA-L]) - k_off*[DNA-L]

Solving, we get: [DNA-L] = [TotalDNA][L] / (k_off/k_on + L)

Usually, we define the dissociation constant to be: kD = k_off/k_on

So we end up with:

[DNA-L] = [TotalDNA][L] / (kD + L)
Personal tools